Theater production on the network economy: The case of crowdfunding of the Cia. Luis louis - Oliveira, Taiguara Belo de [UNESP] (Univ Federal Sergipe, 2015)
This article presents an exploratory study on the relationship between theatrical production and web platforms for collective financing, known as crowdfunding. It examines the experience of Cia. Luis Louis, Sao Paulo-SP, which successfully promoted his campaign by the Catarse, better known crowdfunding platform in Brazil. Data were collected through interviews conducted with members of the company, documents, notes and research information provided by Catarse own. Finally, we point out some reasons, inbuilt at the logic of networks, to counter the affirmation of the crowdfunding as plural and democratic model of funding.
Keywords: theater; crowdfunding; cultural policies; social networks